"Sinking" or sinking?: Identity salience and shifts in Black women's athletic performance. (November 2018) - Howard, Simon; Borgella, Alex
Abstract: Objectives: Based on the theories of stereotype threat and stereotype boost, this study explored the influence of identity salience on athletic performance of individuals (i.e., Black women) who possess one identity that is negatively stereotyped and one identity that is positively stereotyped in the domain of athletics. Black women's racial identity is positively stereotyped in regard to athletic performance, whereas their gender identity is negatively stereotyped. Design: We used a between subjects design with three conditions (race salient, gender salient, and control). Athletic performance served as the dependent measure. Method: Black women basketball players ( N  = 91) were randomly assigned to one of three identity salience conditions: race salient, gender salient, or age salient (control). Social identities were made salient by having participants complete a questionnaire before attempting to shoot free-throws. Results: Participants whose racial identity before shooting free-throws was made salient had significantly better free-throw accuracy than both participants whose gender identity or age identity was made salient. Additionally, participants whose gender identity was made salient performed significantly worse than participants in the control condition. Conclusion: Identity salience can play a role in either improving (i.e., stereotype boost effect) or harming (e.g., stereotype threat effect) athletic performance within the same individual. Future directions involving other individuals who possess both positively and negatively stereotyped social identities' in a particular sports domain, such as Asian male basketball players are discussed. Highlights: Identity salience can play a role in either improving or harming athletic performance within the same individual. Black women primed with their race had better athletic performance than those primed with their age or gender. Black women primed with their gender had worse performance than those primed with age.